A Theoretical Matrix to Approach Literary Texts in the Foreign Language Classroom - Querido, Pedro (2018)
This article is based on my report for the Faculty of Social and Human Sciences of the New University of Lisbon which accounted for my Supervised Teaching Practice of English and German at the German School of Lisbon. In it the advantages of using a theoretical matrix when working with literary texts in a foreign language classroom are listed. After the necessary review of relevant research, the blueprint of one such matrix is put forth. With the Reader Response Theory as its cornerstone, it sets out to develop textual competences, reading strategies and interpretation and critical analysis skills through a management of the learnerreaders’ responses. This approach is best embodied by a multifaceted treatment of scrupulously chosen literary texts which should be oriented by a few guiding principles. Such treatment implies not only an open yet moderated discussion of the text but also a number of procedures which rely on different interaction patterns and promote the development of different skills and competences. The article ends with a short summary and discussion of some lessons which illustrate this theory in practice.